Quality evaluation of cuko pempek based on physics and chemical properties and sensory acceptance - Nico Syah Putra; Ikawati Karim; Fatimah Fatimah; Idealistuti Idealistuti; Eka Rizki Meiwinda; Erni Hawayanti; Harum Sahara; Muhammad Aditya Prawira (AGROINTEK, 2026)
This study investigated the relationship between physics and chemical properties and sensory quality of cuko pempek, a traditional chili–tamarind sauce from Palembang, and assessed its potential contribution to micronutrient intake. Ten samples of cuko from different small-scale producers were analyzed for fructose, moisture, viscosity, and sensory attributes. Correlation and regression analyses revealed that fructose, viscosity, and moisture jointly explained about 70% of the variance in taste preference, with fructose emerging as the dominant driver of consumer acceptance. Principal Component Analysis (PCA) further identified a single quality dimension defined by fructose and viscosity, confirming the close integration of chemical and sensory characteristics. Secondary data analysis showed that a 15 g serving of cuko pempek contributes approximately 0.30–0.38 mg Fe (4–5% RDA), 0.03–0.15 mg Zn (1–5% RDA), and 1.8–8 mg vitamin C (12–50% RDA) for children aged 1–5 years. While modest in absolute terms, vitamin C from tamarind and chili enhances non-heme iron absorption from fish-based pempek, positioning cuko pempek as not only a flavor enhancer but also a functional condiment. In conclusion, cuko pempek quality is primarily determined by fructose concentration and viscosity, while its micronutrient profile—particularly vitamin C—supports improved iron bioavailability. Standardizing formulation and exploring targeted fortification (Fe, Zn) represent practical strategies to maximize both sensory quality and nutritional impact. These findings suggest that cuko pempek holds potential as a culturally relevant food to support nutrition-sensitive interventions, including stunting prevention in Indonesia.